(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In the context of deepening and broadening international economic integration, international arbitration has become a common and effective method for resolving commercial disputes. However, the actual enforceability of an international arbitral award primarily depends on its ability to be recognized and enforced in the countries where the losing party’s assets are located. Vietnam, as a member of the 1958 New York Convention, has established certain legal provisions to govern this matter. But in practice, there are still inadequacy of procedures, jurisdiction, and legal interpretation, which affect the effective enforcement of international arbitral awards. This article focuses on researching the legal experiences and practical enforcement of international arbitral awards in several typical countries, such as the United Kingdom, South Korea, and China. Based on the comparison and analysis, the article proposes a number of recommendations aimed at improving Vietnam’s legal framework, thereby enhancing the reputation and attractiveness of Vietnam’s legal environment for international investment and trade activities.